The re-establishment of Pinus patula Schlect. & Cham. on a pulpwood rotation in Swaziland - Germishuizen, P. J (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- University of Stellenbosch, 1979.